Enhancing Flexibility of 2D Planar Materials By Applying Cut Patterns For Hands On Study Models - Alaçam, Sema; Bacınoğlu, Zeynep; GÜZELCİ, ORKAN ZEYNEL (My University, 2016)
Active experimentation during intertranslations between digital and physical modelling allow designers to explore new geometrical possibilities. Particularly, while changing the strength of the material, cut operations augment bending performance of the planar surfaces. Keeping in mind the potentiality of bending behavior as a generative tool for computational process, this paper presents the findings of three phased experimentation: implication of cut patterns to 2D planar material, mapping 2D patterns onto 3D surfaces and exploring new 3D free-form surfaces.
Keywords: Bending; Hands-on Exploration; Making; Laser Cut; Double Curvature